All Days 2009
DOI: 10.2118/121450-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Reservoir Hydrocarbon Capacity Through Measurement of the Minimum Capillary Entry Pressure of Shale Cap-Rocks

Abstract: Shales play a major role in petroleum exploration and production because they occur both as source rocks and caprocks. Their small pore throat size means that very high capillary pressures are required to establish any hydrocarbon saturation in the shales. The minimum capillary entry pressure (trap capacity) defines the maximum height of a hydrocarbon column that can be trapped by a shale.In this paper, pressure transmission tests were used to experimentally measure capillary entry pressures of various non-wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A two-phase fluid flow drainage process is induced through the rock sample in a triaxial cell, which reproduces the in situ confining pressure and stress conditions acting on the rock [10]. The test can be performed and interpreted according to different experimental procedures and approaches [11][12][13]; generally, mercury-air or nitrogen-water systems are utilized in lab experiments and the results are then corrected according to the real gas-water characteristics. A detailed literature review of threshold pressure measurement can be found in [14].…”
Section: Threshold Pressurementioning
confidence: 99%
“…A two-phase fluid flow drainage process is induced through the rock sample in a triaxial cell, which reproduces the in situ confining pressure and stress conditions acting on the rock [10]. The test can be performed and interpreted according to different experimental procedures and approaches [11][12][13]; generally, mercury-air or nitrogen-water systems are utilized in lab experiments and the results are then corrected according to the real gas-water characteristics. A detailed literature review of threshold pressure measurement can be found in [14].…”
Section: Threshold Pressurementioning
confidence: 99%
“…A two-phase fluid flow drainage process is induced through the rock sample in a triaxial cell, which reproduces the in situ confining pressure and stress conditions acting on the rock [8]. The test can be performed and interpreted according to different experimental procedures and approaches [9][10][11]; generally, mercury-air or nitrogen-water systems are utilized in lab experiments and the results are then corrected according to the real gas-water characteristics. A detailed literature review of threshold pressure measurement can be found in [12].…”
Section: Threshold Pressurementioning
confidence: 99%
“…At the initial stage, when the nonwetting fl uid pressure increases above the capillary entry pressure P c,entry , the rock is partly saturated with this fl uid. The capillary entry pressure, is a pressure above which the wetting phase is displaced from the unconnected pore canals of the largest diameter at the interface [2]. Exceeding of this characteristic pressure value allows migration of the nonwetting phase to the system of pores in the sealing rock, though the nonwetting fl uid is not observed to fl ow yet.…”
Section: Mechanism Of Hydrocarbon Migration Through Non-homogeneous Rmentioning
confidence: 99%